Improved Public Services and Tax Compliance of Small and Medium Scale Enterprises in Nigeria: A Generalised Ordered Logistic Regression - Areo, Oluwafadekemi S; Gershon, Obindah; Osabuohien, Evans (Asian Economic and Financial Review, 2020)
In this paper, we assess tax compliance among small and medium scale enterprises (SMEs) in Nigeria from the perspective of improving public goods and services. We utilise the Nigerian Economic Summit Group (NESG) 2018 Firms Survey Dataset on taxpayers' perception and attitudes and estimate the model of this research using the Generalised ordered logistic regression analysis. This methodology relaxes the assumption of equal odds as the explanatory variables increase. The results show a positive relationship between improved public goods and services and tax compliance of SMEs in Nigeria. However, the analysis reveals that a small increase in the improvement of public goods has a higher likelihood of moving SMEs to become low tax compliant than being tax compliant. We also find that the public goods with the highest likelihood of improving tax compliance of SMEs in Nigeria are public transport, security, and law courts. Furthermore, the findings reveal a significant positive relationship between Tax compliance of SMEs in Nigeria and tax knowledge, tax penalty, and trust in the government. The paper concludes that policymakers in Nigeria should revisit tax policies geared at improving Tax compliance of SMEs. The steps should include properly combining economic and psychological factors based on the extent to which tax non-compliant SMEs can be moved to become tax compliant.